Assessment, investigation, and management of acute monoarthritis. Issue 5 (1st September 1999) - Till, S H; Snaith, M L
Abstract : Trauma is the commonest cause of acute monoarticular joint pain and swelling in patients attending an accident and emergency (A&E) department. However, in a significant minority of patients there will be no history of trauma and consequently a different approach to assessment and investigation is required. Our aim is to offer an outline of how to assess, investigate, and manage a patient with monoarthritis. Despite advances in antibiotic treatment diagnostic delay partly explains why septic arthritis is still associated with considerable morbidity and mortality. It is therefore imperative that joint infection is considered above all other diagnoses. Arthrocentesis is a relatively safe procedure and doctors in A&E medicine are encouraged to develop the skills required to aspirate large joints. In the same way that the A&E department is often portrayed as the shop window of a hospital, the joint can reflect a wide variety of internal diseases. Connective tissue disease, inflammatory bowel disease, sarcoidosis, and vasculitis can all present with a monoarthritis. A non-specific reactive monoarthritis may be a feature of a wide variety of common and uncommon infections including, brucellosis, Lyme disease, and leptospirosis. Drugs are also associated with acute arthritis either through their metabolic consequences or as idiosyncratic drug reactions. The ability for the joint to reflect multisystem disease necessitates close liaison with specialists from other fields. A multidisciplinary approach to the management of these patients is strongly encouraged as some will have unusual diseases that require specialist advice. It is not difficult to appreciate how the patient with monoarthritis can present the clinician with a fascinating diagnostic and therapeutic challenge, which we hope this article will help to unravel.